2012
DOI: 10.1097/id.0b013e31826371b5
|View full text |Cite
|
Sign up to set email alerts
|

Labial Bone Thickness in Area of Anterior Maxillary Implants Associated with Crestal Labial Soft Tissue Thickness

Abstract: Based on this study, CLSTT and ILBT were highly associated in the anterior maxillary region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 36 publications
0
36
1
Order By: Relevance
“…We also found FABr at this level to increase from a mean of 0.39 ± 0.70 mm at the central incisor region to 0.74 ± 1.03 mm at the second premolar region. This is substantially lower than the mean facial bone thickness of 1.28 mm at the same level reported by Roe, et al, (2012) for implants placed 1 year following maxillary anterior single immediate implant placement and 1.79 ± 0.68 mm reported by Le and Borzabadi-Farahani (2012) 4 months post-operatively.…”
Section: Chapter V Discussioncontrasting
confidence: 42%
“…We also found FABr at this level to increase from a mean of 0.39 ± 0.70 mm at the central incisor region to 0.74 ± 1.03 mm at the second premolar region. This is substantially lower than the mean facial bone thickness of 1.28 mm at the same level reported by Roe, et al, (2012) for implants placed 1 year following maxillary anterior single immediate implant placement and 1.79 ± 0.68 mm reported by Le and Borzabadi-Farahani (2012) 4 months post-operatively.…”
Section: Chapter V Discussioncontrasting
confidence: 42%
“…First, although no prior reports of a GBR procedure resulting in clinical increases of both keratinized tissue height and gingival thickness were found in the dental literature by the present authors, a limited number of retrospective studies 13,42 have reported an increase in soft tissue thickness around dental implants primarily in the anterior maxilla after increasing the thickness of the facial bone through GBR. Further research is needed to understand these observed correlations between bone and soft tissue thickness.…”
Section: Management Of Implant Labial Mucosal Recessionmentioning
confidence: 69%
“…11 As labial bone thickness resorbs, there is a corresponding loss in labial soft tissue thickness around the implant. [12][13] Moderate recession can make thin, pink gingival tissues appear dark due to the presence of the underlying metal abutment and implant, and further bone loss can cause unsightly metal exposure above the gingival margin. In general, implants carry a higher risk of soft tissue complications when placed in thin tissue biotypes or with labial inclinations when the labial plate thickness is <2 mm.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations